What Happened to U.S. Business Dynamism? - Ufuk Akcigit; Sina T. Ates (Center for Economic Studies and ifo Institute (CESifo), 2019)
In the past several decades, the U.S. economy has witnessed a number of striking trends that indicate a rising market concentration and a slowdown in business dynamism. In this paper, we make an attempt to understand potential common forces behind these empirical regularities through the lens of a micro-founded general equilibrium model of endogenous firm dynamics. Importantly, the theoretical model captures the strategic behavior between competing firms, its effect on their innovation decisions, and the resulting “best versus the rest” dynamics. We focus on multiple potential mechanisms that can potentially drive the observed changes and use the calibrated model to assess the relative importance of these channels with particular attention to the implied transitional dynamics. Our results highlight the dominant role of a decline in the intensity of knowledge diffusion from the frontier firms to the laggard ones in explaining the observed shifts. We conclude by presenting new evidence that corroborates a declining knowledge diffusion in the economy. We document a higher concentration of patenting in the hands of firms with the largest stock and a changing nature of patents, especially in the post-2000 period, which suggests a heavy use of intellectual property protection by market leaders to limit the diffusion of knowledge. These findings present a potential avenue for future research on the drivers of declining knowledge diffusion.
Keywords: E22; E25; L12; O31; O33; O34; 330; business dynamism; market concentration; competition; knowledge diffusion; step-by-step innovations; transitional dynamics